Effects of compression ratio on variation of stresses and residual oil of cake in pressing process of castor beans and its curve fitting - Liu, Ru-kuan; Xu, Fang-lei; Xiao, Zhi-hong; Li, Chang-zhu; Li, Hui; Zeng, Fan-tao; Ye, Hong-qi (Journal of Central South University, 2015)
The relationships among compression ratio and stress, compression ratio and residual oil of cake in pressing process of castor beans were studied using the test equipment under different states of oilseeds and ways of pressing manners. The results show that variation of stress increases nonlinearly and residual oil rate decreases with the increase of compression ratio. Lower residual oil of cake was obtained by pressing gently and frequently. Curve fitting on both relationships had been built and parameters for the model were obtained by least square procedure and deepening research on pressing process of the castor beans for castor oil. By assuming that the value of oil production is equivalent to the value of energy consumption, the critical compression ratio of intact seeds is 6.2 while that of crushed seeds is 3.6.